REVIEW: Charcoal function and management in boreal ecosystems. Issue 5 (30th July 2013) - Hart, Stephen; Luckai, Nancy
Summary: Charcoal plays an important role in soil function and carbon storage in fire‐prone ecosystems. Charcoal is present in most boreal forest soils as a result of naturally recurring wildfires, which convert 0·7–2% of biomass to charcoal. In boreal forests, charcoal represents 8–10% of soil carbon and 1 pg of carbon globally. Charcoal is resistant to decay, representing a form of super‐passive carbon, with half‐lives one to two orders of magnitude greater than those of other soil organic matter. High concentrations of negative surface charges increase nutrient retention, impacting boreal soil function, productivity and species composition. Due to a lack of soil mixing processes, charcoal in boreal soils is vulnerable to recombustion in recurring fires, inhibiting the accumulation of charcoal over time, unlike in other fire‐prone ecosystems. Boreal charcoal stocks are highly variable. Increased fire intensity results in greater charcoal formation, with stand‐replacing crown fires resulting in much larger charcoal stocks than non‐stand‐replacing ground fires. Current estimates of carbon storage based on Scandinavian studies of non‐stand‐replacing fires may underestimate charcoal stocks by factors of 2–3. Synthesis and applications . Charcoal contributes to boreal soil function, ecosystem productivity, nutrient retention and carbon cycling. In the absence of fire, charcoal loses many active properties, contributing to declining productivity with increasing time since fire. Incorporation of charcoal into ecosystem management using prescribed burns may contribute to sustainable management of boreal forests and maintaining global carbon cycles. Abstract : Charcoal contributes to boreal soil function, ecosystem productivity, nutrient retention and carbon cycling. In the absence of fire, charcoal loses many active properties, contributing to declining productivity with increasing time since fire. Incorporation of charcoal into ecosystem management using prescribed burns may contribute to sustainable management of boreal forests and maintaining global carbon cycles.